A difference technique to avoid interface errors in measurement of high-conductance thermal insulation. (May 2017) - Clarke, Robin E; Shabani, Bahman; Rosengarten, Gary
Lower limits of measurement are prescribed within all steady-state test methods for thermal insulation. The limit, typically 0.1 m 2  K/W, is largely required because of the increasing significance of interface resistance. We have previously proposed the use of a difference method, in conjunction with flexible buffer materials, to minimize the effects of interface resistance and facilitate measurement of rigid materials below these limits. We have now studied this approach at higher thermal resistances and incorporated a refinement to include a known reference specimen in the difference measurement, which largely eliminates the residual resistance terms. Specimens of expanded polystyrene and cast acrylic were measured in a conventional heat flow meter apparatus using two alternative silicone buffer materials: one solid and the other a sponge. Analysis also included earlier measurements of 12 more highly conducting specimens. Across all of these, thermal resistance values obtained by the difference method were lower between 0.008 and 0.016 m 2  K/W, attributable to removing the contribution of interface resistance.